The Olympic Regeneration in East London (ORiEL) study: protocol for a prospective controlled quasi-experiment to evaluate the impact of urban regeneration on young people and their families. Issue 4 (29th August 2012) - Smith, Neil R; Clark, Charlotte; Fahy, Amanda E; Tharmaratnam, Vanathi; Lewis, Daniel J; Thompson, Claire; Renton, Adrian; Moore, Derek G; Bhui, Kamaldeep S; Taylor, Stephanie J C; Eldridge, Sandra; Petticrew, Mark; et al.
Abstract : Introduction: Recent systematic reviews suggest that there is a dearth of evidence on the effectiveness of large-scale urban regeneration programmes in improving health and well-being and alleviating health inequalities. The development of the Olympic Park in Stratford for the London 2012 Olympic and Paralympic Games provides the opportunity to take advantage of a natural experiment to examine the impact of large-scale urban regeneration on the health and well-being of young people and their families. Design and methods: A prospective school-based survey of adolescents (11–12 years) with parent data collected through face-to-face interviews at home. Adolescents will be recruited from six randomly selected schools in an area receiving large-scale urban regeneration (London Borough of Newham) and compared with adolescents in 18 schools in three comparison areas with no equivalent regeneration (London Boroughs of Tower Hamlets, Hackney and Barking & Dagenham). Baseline data will be completed prior to the start of the London Olympics (July 2012) with follow-up at 6 and 18 months postintervention. Primary outcomes are: pre–post change in adolescent and parent mental health and well-being, physical activity and parental employment status. Secondary outcomes include: pre–post change in social cohesion, smoking, alcohol use, diet and body mass index. The study will account for individual and environmental contextual effects in evaluating changes to identified outcomes. A nested longitudinal qualitative study will explore families' experiences of regeneration in order to unpack the process by which regeneration impacts on health and well-being. Ethics and dissemination: The study has approval from Queen Mary University of London Ethics Committee (QMREC2011/40), the Association of Directors of Children's Services (RGE110927) and the London Boroughs Research Governance Framework (CERGF113). Fieldworkers have had advanced Criminal Records Bureau clearance. Findings will be disseminated through peer-reviewed publications, national and international conferences, through participating schools and the study website (http://www.orielproject.co.uk ).